Salmon P. Chase : a biography - Niven, John. (New York : Oxford University Press, 1995)
A biography of Salmon P. Chase, one of the principal political figures in the American Civil War period. A rival to Abraham Lincoln for the Republican Presidential nomination in 1860, he subsequently became Secretary of the Treasury in Lincoln's war-time cabinet.
1. Threshold; 2. Trials and Triumphs; 3. The Young Professional; 4. Upward Bound; 5. A Distant Shore; 6. To Recognize the Distinctions; 7. Climbing the Slippery Pole; 8. "Free Soil, Free Labor and Free Men, "; 9. Among the Great; 10. Mid-passage; 11. Independent Democrat; 12. An Uncertain Future; 13. On the Campaign Trail; 14. As Others See Us; 15. For the Good of the Party; 16. Defeat at the Summit; 17. Visit to Springfield; 18. Loaves and Fishes; 19. War; 20. No Other Recourse; 21. Military Moves and Missions; 22. High Stakes; 23. Emancipation with Exceptions; 24. Mixed Results.
Includes bibliographical references (pages 459-528) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Chase, Salmon P. -- 1808-1873.; United States. -- Congress. -- Senate -- Biography; États-Unis. -- Congress. -- Senate -- Biographies; Chase, Salmon P. -- 1808-1873; United States. -- Congress. -- Senate; Legislators -- United States -- Biography; Judges -- United States -- Biography; Governors -- Ohio -- Biography; United States -- Politics and government -- 1849-1877.; Parlementaires -- États-Unis -- Biographies; Juges -- États-Unis -- Biographies; Gouverneurs -- Ohio -- Biographies; États-Unis -- Politique et gouvernement -- 1849-1877.; HISTORY -- State & Local; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- State & Local -- General; Governors; Judges; Legislators; Politics and government; Ohio; United States; 1849-1877; Politics -- History, 1845-1901; Biographies; Biographies; Biographies